Intrapleural fibrinolysis and DNase versus video-assisted thoracic surgery (VATS) for the treatment of pleural empyema (FIVERVATS): protocol for a randomised, controlled trial – surgery as first-line treatment. Issue 3 (9th March 2022) - Christensen, Thomas Decker; Bendixen, Morten; Skaarup, Søren Helbo; Jensen, Jens-Ulrik; Petersen, Rene Horsleben; Christensen, Merete; Licht, Peter; Neckelmann, Kirsten; Bibby, Bo Martin; Møller, Lars B; Bodtger, Uffe; Borg, Morten Hornemann; et al.
Abstract : Introduction: Pleural empyema is a frequent disease with a high morbidity and mortality. Current standard treatment includes antibiotics and thoracic ultrasound (TUS)-guided pigtail drainage. Simultaneously with drainage, an intrapleural fibrinolyticum can be given. A potential better alternative is surgery in terms of video-assisted thoracoscopic surgery (VATS) as first-line treatment. The aim of this study is to determine the difference in outcome in patients diagnosed with complex parapneumonic effusion (stage II) and pleural empyema (stage III) who are treated with either VATS surgery or TUS-guided drainage and intrapleural therapy (fibrinolytic (Alteplase) with DNase (Pulmozyme)) as first-line treatment. Methods and analysis: A national, multicentre randomised, controlled study. Totally, 184 patients with a newly diagnosed community acquired complicated parapneumonic effusion or pleural empyema are randomised to either (1) VATS procedure with drainage or (2) TUS-guided pigtail catheter placement and intrapleural therapy with Actilyse and DNase. The total follow-up period is 12 months. The primary endpoint is length of hospital stay and secondary endpoints include for example, mortality, need for additional interventions, consumption of analgesia and quality of life. Ethics and dissemination: All patients provide informed consent before randomisation. The research project is carried out in accordance with the Helsinki II Declaration, European regulations and Good Clinical Practice Guidelines. The Scientific Ethics Committees for Denmark and the Danish Data Protection Agency have provided permission. Information about the subjects is protected under the Personal Data Processing Act and the Health Act. The trial is registered at www.clinicaltrials.gov, and monitored by the regional Good clinical practice monitoring unit. The results of this study will be published in peer-reviewed journals and presented at various national and international conferences. Trial registration number: NCT04095676 .